The Democratic Republic of the Congo - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
According to the updated Low-Income Country Debt Sustainability Framework (LIC DSF), the Democratic Republic of the Congo (DRC)’s debt-carrying capacity was assessed as weak. DRC remains at a moderate risk of external and overall debt distress, with limited space to absorb shocks. The debt coverage has been improved since the last DSA, especially on domestic debt. The external nominal debt ratios are lower than at the time of the 2015 debt sustainability analysis (DSA), however the country shows vulnerability in debt repayment capacity, even under the baseline, due to weak revenue mobilization. Most external debt thresholds are breached under the stress tests, highlighting the country’s vulnerability to external shocks. Given limited buffers, prudent borrowing policies are essential by prioritizing concessional loans and strengthening debt management policies